2016
DOI: 10.5812/ijp.5229
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Automated Auditory Brainstem Response and Otoacoustic Emission in Universal Neonatal Hearing Screening

Abstract: Background: During the last decade, the rapid expansion of universal neonatal hearing screening (UNHS) has brought into focus questions about the most appropriate screening technology for this indication. Objectives:The main aim of this study was to examine the cost-effectiveness of automated auditory brainstem response (AABR) and otoacoustic emissions (OAE) in universal neonatal hearing screening programs. Methods: This economic study was performed in Iran. A decision tree model was applied for economic evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…This review observed that diagnostic accuracy of OAEs and ABRs, the most commonly used screening methods, varied widely across the evaluations. The sensitivity of OAEs ranged between 77% [48] and 100% [37] and that of ABRs ranged between 80% [37] and 98% [46] (see Table 3). The specificity values of OAEs ranged between 84% [46] and 99% [33] and that of ABRs ranged between 90% [42] and 97% [52].…”
Section: Methodological Differences: Screening and Diagnostic Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…This review observed that diagnostic accuracy of OAEs and ABRs, the most commonly used screening methods, varied widely across the evaluations. The sensitivity of OAEs ranged between 77% [48] and 100% [37] and that of ABRs ranged between 80% [37] and 98% [46] (see Table 3). The specificity values of OAEs ranged between 84% [46] and 99% [33] and that of ABRs ranged between 90% [42] and 97% [52].…”
Section: Methodological Differences: Screening and Diagnostic Strategymentioning
confidence: 99%
“…The specificity values of OAEs ranged between 84% [46] and 99% [33] and that of ABRs ranged between 90% [42] and 97% [52]. Only one evaluation estimated testing accuracy from a meta-analysis [52]. The other evaluations based estimates of testing accuracy on a single study.…”
Section: Methodological Differences: Screening and Diagnostic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding neonatal hearing screening, OEA exhibited sensitivity of 0.77 (confidence interval [CI] 95% 0.65-0.86) and specificity of 0.93 (CI 95% 0.92-0.93), and a-ABR exhibited sensitivity of 0.93 (CI 95% 0.87-0.96) and specificity of 0.97 (CI 95% 0.96-0.98), compared with ABR. 15 Audiometry is the gold standard for hearing loss diagnoses, but FS-ABR is considered an accurate test to estimate hearing thresholds in infants that cannot cooperate with audiometry. 16,17 Neurodiagnostic ABR is used to verify the conductibility of the auditory pathways.…”
Section: Methodsmentioning
confidence: 99%